Prevention and Resolution of Sovereign Debt Crises - Ams, Julianne; Asonuma, Tamon; Bergthaler, Wolfgang; DeLong, Chanda (Washington, D.C. : International Monetary Fund, 2018)
'The IMF's Role in the Prevention and Resolution of Sovereign Debt Crises' provides a guided narrative to the IMF's policy papers on sovereign debt produced over the last 40 years. The papers are divided into chapters, tracking four historical phases: the 1980s debt crisis; the Mexican crisis and the design of policies to ensure adequate private sector involvement ('creditor bail-in'); the Argentine crisis and the search for a durable crisis resolution framework; and finally, the global financial crisis, the Eurozone crisis, and their aftermaths.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet